2014
DOI: 10.1103/physreva.90.063632
|View full text |Cite
|
Sign up to set email alerts
|

Metastable spin textures and Nambu-Goldstone modes of a ferromagnetic spin-1 Bose-Einstein condensate confined in a ring trap

Abstract: We investigate the metastability of a ferromagnetic spin-1 Bose-Einstein condensate conhned in a quasi-onedimensional rotating ring trap by solving the spin-1 Gross-Pitaevskii equation. We find analytical solutions that exhibit spin textures. By performing linear stability analysis, it is shown that the solutions can become metastable states. We also find that the number of Nambu-Goldstone modes changes at a certain rotation velocity without changing the continuous symmetry of the order parameter.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Modulation instability of spinor BECs in a ring geometry has been studied theoretically in Ref. [36]. Let us substitute the cw trial function (7) into the dynamical equations (2).…”
Section: A Continuous Wave Solutionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Modulation instability of spinor BECs in a ring geometry has been studied theoretically in Ref. [36]. Let us substitute the cw trial function (7) into the dynamical equations (2).…”
Section: A Continuous Wave Solutionsmentioning
confidence: 99%
“…[40][41][42][43][44]. In the context of mean field theory, sound waves (or by other names, acoustic waves, phonons, or Bogoliubov excitations) and also MI (where sound waves have complex-valued frequencies) may be represented by small perturbations to a cw solution [17,33,35,36,[45][46][47][48][70][71][72][73],…”
Section: B Sound Waves and Modulational Instabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The population imbalance and fixed phase relation between multiple components bring persistent flows novel stability features [18][19][20][21][22]. It has been found that rich phase diagram and interesting collective excitations can exist in interacting two-component [23][24][25][26] and three-component [27][28][29] toroidal BECs.…”
Section: Introductionmentioning
confidence: 99%